(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
India is a rapidly developing powerhouse, but its centuries-old caste system has earned it a badreputation. In this study, we look back at the oppressors, the oppressed, and the beginnings of Dalitliterature. Examining the development and reach of Dalit literature is a part of this. All Dalit literary works,it is commonly held, may be traced back to the ideas of Dr. B. R. Ambedkar. The study analyses the harshcircumstances of the Dalit community and their admirable efforts to improve their social standing.Dramatic depictions of the social and political experiences of the Dalit population in India’s caste systemare presented in this literature. It follows the lives of Dalits in India and their relationships with others, bothwithin the Dalit community and outside of it. It delves into the fight for freedom and equality by the Dalitpeople. Positive attitudes towards equality may be found in the social life of the Dalit community todaythanks to powerful Dalit movements, the hammering on upper caste society by authors and intellectualsin Dalit literature, and the implementation of welfare packages by the Government. Caste and genderbaseddiscrimination are both illegal. Through literature, the downtrodden take us on a journey from thesearch for identity to full inclusion in society.